Research progress of umami substances in soy sauce and their detection methods - WANG Zhen, CHEN Chao, JI Xiaomeng, REN Nan, ZHAO Wentao, WANG Jiangyue, LIU Xinyi, GUO Wenping (Zhongguo niangzao)
Soy sauce is very popular in China because of its unique freshening effect. In this paper, using the umami substances in soy sauce as the research object, the various umami substances contained in soy sauce such as amino acids, nucleotides, umami peptides and organic acids were summarized, and their detection methods were summarized. Meanwhile, the current evaluation methods of umami substances at home and abroad were summarized, in order to combine the detection and evaluation methods of umami substances and provide references for further research on umami substances in soy sauce.